Comparison of early postoperative outcomes between omega-like duct-to-mucosa pancreatojejunostomy and conventional duct-to-mucosa pancreatojejunostomy after pancreaticoduodenectomy. Issue 5 (May 2022) - Zheng, Minghui; Liu, Anan; Li, Judong; Liang, Xing; Peng, Junfeng; Chen, Danlei; Shi, Ligang; Fu, Zhiping; Ji, Meng; Yang, Guang; Yang, Tianbo; Tang, Liang; et al.
Abstract: Background: Pancreatic fistula is a life-threatening complication of pancreaticoduodenectomy. Omega-like duct-to-mucosa pancreatojejunostomy is a novel technique which helps reduce the risk of fistulation. This study aimed to compare early postoperative outcomes of omega-like and conventional pancreatojejunostomy. Methods: A retrospective single-centre cohort study comparing outcomes of adult patients who underwent open pancreatoduodenectomy with conventional (CDMP) or omega-like duct-to-mucosa pancreatojejunostomy (ODMP) between 1 January 2015 and 31 December 2019. The primary outcome measure was the pancreatic fistula rate. Results: 440 patients were included in this study of whom 233 underwent CDMP and 207 ODMP. The rate of clinically relevant pancreatic fistula (grade B/C) was significantly higher after CDMP than ODMP (18.5% vs. 10.6%, P  = 0.021). 153 patients in CDMP group and 99 patients in ODMP group developed one or more complications (65.7% vs. 47.8%, P  = 0.004). The average hospitalization expenses were numerically decreased in ODMP group, although this was not statistically significant (120, 000 ± 42, 000 [Chinese Yuan] vs. 100, 000 ± 40, 000 [Chinese Yuan] or 18, 581 ± 6503 [United States Dollar] vs. 15, 484 ± 6194 [United States Dollar], P  = 0.402). Conclusion: ODMP may reduce the incidence of pancreatic fistula and other early postoperative complications after pancreatoduodenectomy.